Dekonstruksi dan Rekonstruksi Filsafat Kebijakan Merdeka Belajar Berbasis Ilmu Sosial Profetik Kuntowijoyo - Alif Rizky Ramadhan; Amin Fauzi (Universitas Muhammadiyah Prof Dr Hamka, 2024)
The Merdeka Belajar curriculum is a curriculum that is tasked with complementing and simplifying the 2013 curriculum. However, in practice, various problems arise that are very theoretical to applicative. This can be seen from how the philosophical basis that develops in this curriculum is very thick with an understanding of western epistemology which in practice emphasizes the essence of forward-looking education without looking at the roots of existing educational traditions. From the above, this research will examine how the need for an effort to deconstruct the current Merdeka Belajar policy. Then, this research also examines how the results of the deconstruction are used as a basis for carrying out a reconstruction of the philosophy of the principles of the Merdeka Belajar curriculum policy through a review based on the prophetic social science epistemology built by Kuntowijoyo. The research methodology will be through a qualitative research approach and literature study, as well as the use of Derrida's deconstruction theory. The results of this study show that in building a national education policy that is humanist, liberative, transcendent in its application, an education policy principle is needed that also looks at the world in a theoantrposcentric perspective between divinity and humanity in all aspects of life. The contribution of this research is the researcher's effort to try to propose a hypothesis in the formation of the prophetic philosophical principles of the new Merdeka Belajar policy based on prophetic social science thought.